INTERNET ENVIRONMENTAS A TOOL FOR FORMING NONTOCRATIC PUBLIC GOVERNANCE - Storozhenko, Lina (Collection of scientific papers «ΛΌГOΣ», 2023)
In the conditions of the information society, modern political, economic, cultural, social life is acquiring a new vector of development, in which network communication is the most important factor in the formation of a new type of society, which, thanks to horizontal communication on the Internet, becomes independent of state power in information and communication aspects.